Biased acquisition of spacers by the CRISPR System of the V. cholerae - Supan, Erena Tuzneen; Haque, Nayeema; Momtaz, Monira (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2021.